2021
DOI: 10.1101/2021.02.17.431594
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subventricular zone/white matter microglia reconstitute the empty adult microglial niche in a dynamic wave

Abstract: Microglia, the brain's resident myeloid cells, play central roles in brain defense, homeostasis, and disease. Using sustained colony-stimulating factor 1 receptor inhibition, we report an unprecedented level of microglial depletion and establish a model system that achieves an empty microglial niche in the adult brain. We identify a myeloid cell that migrates from an important neurogenic niche, the subventricular zone, and associated white matter areas. These cells exhibit tremendous chemotaxis potential, migr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 100 publications
(171 reference statements)
2
1
0
Order By: Relevance
“…Importantly, no overt changes in astrocytes were found in this study, as reported previously following pharmacological depletion in wild-type (WT) mice with either CSF1R inhibitor utilized [10,71,73]. Synaptic connectivity and neural activity are both normalized following microglial repopulation [72], which is consistent with the normalization of PNN densities we observed under similar conditions of inhibitor cessation following microglial elimination [216]. Loss of PNNs with disease thus likely reflects a toxic gain-of-function in microglia of this newly identified homeostatic role, whereby augmented or complementary PNN-degradative processes are activated, either via enhanced or alternative secretion of ECM-cleaving proteases or their modulators, and/or increased phagocytosis.…”
Section: Perineuronal Netssupporting
confidence: 90%
See 1 more Smart Citation
“…Importantly, no overt changes in astrocytes were found in this study, as reported previously following pharmacological depletion in wild-type (WT) mice with either CSF1R inhibitor utilized [10,71,73]. Synaptic connectivity and neural activity are both normalized following microglial repopulation [72], which is consistent with the normalization of PNN densities we observed under similar conditions of inhibitor cessation following microglial elimination [216]. Loss of PNNs with disease thus likely reflects a toxic gain-of-function in microglia of this newly identified homeostatic role, whereby augmented or complementary PNN-degradative processes are activated, either via enhanced or alternative secretion of ECM-cleaving proteases or their modulators, and/or increased phagocytosis.…”
Section: Perineuronal Netssupporting
confidence: 90%
“…CTSB is secreted by microglia following LPS activation [265], as is CTSS, which is also upregulated by brain lesion injury [266] and in bulk tissue of 5xFAD mice where we have reported PNN deficits (hippocampus, cortex) [71,90]; it should be noted in the latter case that we did not observe significant upregulation of any Mmp genes in any regions examined [71]. We found that Ctss expression in the brain most closely follows the kinetics of microglial elimination and repopulation [74], which increases [72,73,90] and normalizes [216] PNN density, respectively, and indeed, its transcripts were consistently absent in microglia-depleted brains in our studies [71,73,74,216]. CTSS is functionally stable at the neutral pH of the extracellular space, and under such conditions, it can efficiently degrade CSPGs neurocan and phosphacan, where CTSB at several-fold greater concentrations could not [266].…”
Section: Potential Mechanisms Of Microglial Ecm Regulationmentioning
confidence: 49%
“…Here, we identify specific remodeling states of microglia that persist following CSF1R inhibition showing reduced homeostatic gene expression. Other groups recently found small populations of CSF1Rindependent or repopulating microglia in the brain, and we note similar patterns of gene expression, with reduced homeostatic genes such as Tmem119 and P2ry12, and increased expression of genes such as Lyz2 [34,53]. In these microglia repopulation studies, it was proposed that more immature microglia survive CSF1R inhibition, but microglia maturation may not be a key factor in the context of development since we previously found greater dependence of retinal microglia on CSF1R at embryonic stages than in postnatal retina [19].…”
Section: Discussionsupporting
confidence: 83%